The Effect Of Microwave Pre-treatment On The Antioxidant Activity Of Candlenut Oil Using The DPPH Method: Pengaruh Pra-perlakuan Microwave terhadap Aktivitas Antioksidan Minyak Kemiri dengan Menggunakan Metode DPPH - Lahifah Ramadhaningtyas; Aldi Budi Riyanta; Akhmad Aniq Barlian (Akademi Farmasi Surabaya, 2023)
Candlenut is one of the industrial plant commodities that can be extracted so that the candlenut seeds produce oil with levels of 55-65% of the weight of the seeds. The main components of candlenut oil are saturated and unsaturated fatty acids such as oleic acid which are antioxindants. This study aims to determine the effect of the time factor of using the microwave on the yield of candlenut oil and its antioxidant activity. This research method uses a microwave power intensity of 100 watts with a variation of the microwave time for 60, 90 and 120 seconds. Determination of the antioxidant activity of candlenut oil using reagents 2,2diphenyl-1-picrihydrazil or DPPH. The results of this study indicate that there is an antioxidant activity in candlenut oil given microwave pre-treatment. The results of the antioxidant activity of the candlenut seed extract which were pre-treated with microwave 60, 90, and 120 seconds with IC50 values ​​were 979489.985 g/ml, respectively; 1241,652 g/ml; and 70.307 g/ml. While the yield is 49,75%; 55,7%; and 48,47% which indicates there is a decrease in the yield of thirtd sample. The yield is influenced by the lenght of micorwave irradiation, seed condition, power intensity and oil press. Based on these results, it can be concluded that there is an effect of microwaves on the antioxidant activity of candlenut oil.